A Polyphenol‐rich Pomegranate Fruit Extract Suppresses NF‐κB and IL‐6 Expression by Blocking the Activation of IKKβ and NIK in Primary Human Chondrocytes. (9th March 2017) - Haseeb, Abdul; Khan, Nazir M.; Ashruf, Omer S.; Haqqi, Tariq M.
Abstract : Pomegranate fruit extract (PE) rich in polyphenols has been shown to exert chondroprotective effects, but the mechanism is not established. Here, we used an in vitro model of inflammation in osteoarthritis (OA) to investigate the potential of PE to suppress interleukin 1 beta (IL‐1β)‐stimulated expression of inflammatory cytokine IL‐6, generation of reactive oxygen species (ROS) levels, and investigated the mechanism of NF‐κB inhibition by analyzing the activation of the kinases upstream of IκBα in primary human chondrocytes. Total and phosphorylated forms of kinases and expression of IL‐6 were determined at protein and mRNA levels by western immunoblotting and Taqman assay, respectively. Dihydrorhodamine 123 staining estimated ROS generation. Pomegranate fruit extract inhibited the mRNA and protein expression of IL‐6, generation of ROS, and inhibited the IL‐1β‐mediated phosphorylation of inhibitor of nuclear factor kappa‐B kinase subunit beta (IKKβ), expression of IKKβ mRNA, degradation of IκBα, and activation and nuclear translocation of NF‐κB/p65 in human chondrocytes. Importantly, phosphorylation of NF‐κB‐inducing kinase was blocked by PE in IL‐1β‐treated human OA chondrocytes. Taken together, these data suggest that PE exerts the chondroprotective effect(s) by suppressing the production of IL‐6 and ROS levels. Inhibition of NF‐κB activation by PE was blocked via modulation of activation of upstream kinases in human OA chondrocytes. Copyright © 2017 John Wiley & Sons, Ltd.